Certain properties of normaloid operators - Mogotu, P.O.; Kerongo, J.; Obogi, R. K.; Okelo, Bernad N. (JOOUST)
In this paper we establish new conditions for contractivity of normaloid operators. We employ some results for contractivity due to Furuta, Nakomoto, Arandelovic and Dragomir. A particular generalization is also given.
1st JOOUST Scientific Conference
Keywords: Normaloid operators; Contractive operators; Cauchy-Schwarz inequality; Tensor product.